Thinking, fast and slow [compact disc, unabridged] - Kahneman, Daniel, 1934- (Random House Audio, 2011)
Kahneman's singularly influential work has transformed cognitive psychology and launched the new fields of behavioral economics and happiness studies. In this path-breaking book, he shows how the mind works, and offers practical and enlightening insights into how choices are made in both business and personal lives.